Climate changed : refugee border stories and the business of misery - Briggs, Daniel (Criminologist) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Climate Changed is an honest and humane account about the rapid downsizing of the world's natural resources and the consequences this has for millions of people who, year after year, are displaced from their home countries because of politically-instigated and economically-justified war and conflict. Based on interviews with 110 refugees who arrived into Europe from 2015 to 2018 and observations of refugee camps, border crossings, inner-city slums, social housing projects, NGO and related refugee associations, it offers a moving insight into the refugee experience of leaving home, crossing borders and settling in Europe and sets this against the geo-political and commercial enterprise that dismantled their countries in the international chase for wilting quantities of the world's natural resources. Yet at every point of their journey to their new lives and in the resettlement process, the refugees are on the end of more perpetual victimisation and exploitation as there is always money to be made from them. Even if their labour is in demand, all this is further exacerbated by a European social climate of intolerance and stigma which jeopardises integration and counters their wellbeing and safety. The climate has changed. Students, lecturers and professors and other similar academic workers, policymakers, various practitioners, and voluntary workers within the sector of refugee frontlines as well as aid workers, town planners and welfare support staff would find relevance in this book"--
OCLC-licensed vendor bibliographic record.
Keywords: Immigrants -- European Union countries -- History -- 21st century; Conflict management -- European Union countries; European Union countries -- Emigration and immigration -- Social aspects -- 21st century; European Union countries -- Social policy -- 21st century; SOCIAL SCIENCE / Sociology / General